Serum concentration of ketamine and antinociceptive effects of ketamine and ketamine-lidocaine infusions in conscious dogs - Kaka, Ubedullah; Saifullah, Bullo; Abubakar, Adamu Abdul; Goh, Yong Meng; Fakurazi, Sharida; Kaka, Asmatullah; Behan, Atique Ahmed; Ebrahimi, Mahdi (BioMed Central, 2016)
Background: Central sensitization is a potential severe consequence of invasive surgical procedures. It results in postoperative and potentially chronic pain enhancement. It results in postoperative pain enhancement; clinically manifested as hyperalgesia and allodynia. N-methyl-D-aspartate (NMDA) receptor plays a crucial role in the mechanism of central sensitisation. Ketamine is most commonly used NMDA-antagonist in human and veterinary practice. However, the antinociceptive serum concentration of ketamine is not yet properly established in dogs. Six dogs were used in a crossover design, with one week washout period. Treatments consisted of: 1) 0.5 mg/kg ketamine followed by continuous rate infusion (CRI) of 30 μg/kg/min; 2) 0.5 mg/kg ketamine followed by CRI of 30 μg/kg/min and lidocaine (2 mg/kg followed by CRI of 100 μg/kg/min); and 3) 0.5 mg/kg ketamine followed by CRI of 50 μg/kg/min. The infusion was administered up to 120 min. Nociceptive thresholds and ketamine serum concentrations were measured before drug administration, and at 5, 10, 20, 40, 60, 90, 120, 140 and 160 min after the start of infusion. Results: Maximum concentration recorded was 435.34 ± 26.18 ng/mL, 582.34 ± 227.46 ng/mL and 733.77 ± 133.6 ng/mL for K30, KL30 and K50, respectively. The concentration at 120 min was 250.87 ± 39.87, 221.73 ± 91.03 and 343.67 ± 63.21 ng/mL at 120 min in K30, KL30 and K50, respectively. All the three infusion regimes maintained serum concentrations above 200 ng/mL. The thresholds returned towards baseline values within 20 min, after cessation of infusion. Conclusion: Serum concentration to produce mechanical antinociceptive effects in dogs is between 100 and 200 ng/mL. All the three infusion regimes in this study provided antinociceptive effects throughout the infusions. In this study, we found that the serum concentration of ketamine to produce mechanical antinociceptive effects in dogs is above 200 ng/mL. All three infusion regimes provided antinociceptive effects throughout the infusions without causing harmful effects. Further studies are recommended in a clinical setting.